Characteristics and Distribution of Soils in the Semiarid Basalt Landscape of Western India: A Case Study - S. A. Surwase; P. R. Kadu (Research Advances in Environment, Geography and Earth Science Vol. 9, 2024)
A soil survey has been conducted on the soil topography and topography-soil relationships of the semi-arid region of Western India. In this study, seven terrain profiles representing the topography consisting of mountain peaks, cliffs, side walls, rugged terrains, plains and valleys were studied. The studies show that the terrain development and features follow the topographic patterns. The development of the stratigraphic section is least in the mountains and best in the plains. The horizon observations from the top of the peak to the plain are A-R, Ap-Bw-Cr, Ap-Bw1-Bw2-Bw3-Bw4-Crk, Ap-Bw1-Bw2-Bss1-Bss2-Bss3, Ap-Bw -Bss1-Bss2-Bss3-Bc and Ap-Bw1-Bw2-Bw3-Bw4. The color ranges from brown to dark gray-brown. The depth of the cave varies from very shallow to very deep. Clay content, cation exchange capacity, soil reactivity, electrical conductivity, base saturation and exchangeable cations all increase from mountains to plains. The soil organic carbon increased topographically and varied from the summits to plain and valley. Hill, gable and plain soils are classified as Entisols, Inceptisols and Vertisols, respectively.